Tanggung Jawab Notaris Atas Tindakan Yang Dilakukan Notaris Pengganti Ditinjau Dari Undang-Undang Jabatan Notaris - Efendi Saputra; Moh Saleh (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The notary’s authority to perform a deed of authentification is directly proportional to its responsibilities, because the responsibility remains with the notary even though the notary has entered retirement age. However, it still happens sometimes that notaries still mislead and make mistakes when performing authentic deeds, whether intentionally or not. On October 5, 2020, the Hous of Representatives passed the Omnibus Law on the Job Creation Bill into Law No. 11 of 2020 related to Job Creation (Job Creation Law) in a plenary meeting, which significantly changes the law on setting up a Limited Limited Liability Companies in Indonesia, particularly those regulated in the Limited Liability Company Law. In their respective positions as Notaries and Substitute Notaries if any errors or omissions occur, what is the legal protection for the Substitute Notary and to what extent is the limitation of the liability of the Notary and Substitute Notary? This research uses the Juridical Empirical method. This study result is that if a Notary or Substitute Notary makes a mistake in making an authentic deed that causes harm to other people, as long as the aggrieved party can prove that the mistake was due to the Notary's negligence or intentionality, then the Notary can be held accountable from a civil, criminal or administrative perspective. Similarly, the legal protection received by substitute Notaries receives legal protection that is parallel to the original notary in accordance with their roles and responsibilities in carrying out notary duties.